Noncovalent Interactions in Organocatalysis: Modulating Conformational Diversity and Reactivity in the MacMillan Catalyst1. Issue 31 (21st June 2013) - Holland, Mareike C.; Paul, Shyeni; Schweizer, W. Bernd; Bergander, Klaus; Mück‐Lichtenfeld, Christian; Lakhdar, Sami; Mayr, Herbert; Gilmour, Ryan
<x xml:space="preserve">Abstract</x> Intriguing imidazolidinones! Inspired by noncovalent interactions in proteins, a series of electronically distinct MacMillan catalysts were designed. The effect of electronic modulation on ground state conformation, reactivity, and performance was studied in a catalytic setting with intriguing outcomes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>